An overview of the rationale for qualitative research methods in social health - Stuckey, Heather L. (Journal of Social Health and Diabetes, 2013)
Qualitative research is a primary way to understand the context of diabetes in a person′s life, beyond the medical outcomes. Identifying the qualitative issues such as patients′ knowledge about diabetes, their beliefs and attitudes, and their relationship with health care professionals can serve as data to determine the obstacles and, in turn, resolutions to those issues in diabetes management. Characteristics of qualitative and quantitative methods are described, with the discussion that both methods are complementary, not conflicting, to further the field of diabetes research.
Keywords: Diabetes research; psychosocial issues; qualitative research; research methods; social issues